Legal Regulation of Multinational Corporate Health Services and Local Legal Obligations - Waluyo, Argho; Vitrianingsih, Yeni; Mardikaningsih, Rahayu; Issalillah, Fayola; Negara, Dharma Setiawan (Journal of Social Science Studies, 2024)
The provision of health services by multinational corporations presents legal challenges that require strict regulations to protect the public interest. This study aims to analyse the legal aspects of the provision of health services by multinational corporations in Indonesia, with a focus on licensing, accreditation, and local legal responsibilities. The method used is normative juridical through literature study and analysis of laws and regulations governing the health, investment, and corporation sectors. The results of the study show that Indonesian law places licensing and accreditation as the main obligations that determine the legality of health service operations. Multinational corporations are required to adjust their operational standards to national provisions, including service quality standards, patient safety, and health worker management. Local legal responsibilities include compliance with health regulations, personal data protection, consumer protection, financial accountability, and government oversight mechanisms. This legal framework emphasises that the presence of multinational corporations in the health sector does not diminish national legal sovereignty. This study confirms that legal compliance is a key requirement for healthcare services provided by multinational corporations to be legally accepted and sustainable, while also guaranteeing the protection of people's rights to quality and safe healthcare services.